Biology of Xylocopa (Xylocopa) violacea (L. 1758) (Hymenoptera: Apidae): interaction with Sennertia (Sennertia) cerambycina (Acari: Chaetodactylidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The aim of this contribute are: recording of Sennertia cerambycina (Acari) in Campania, hypopi-X. violacea interactions and some life cycle traits of this mite. Hypopi (deuthoninphs with dorsal shield and catching organs) live on Xylocopa violacea adults (phoretic interaction), mainly on mesosomal metanotum and epinotum and on the first metasomal segment; all these points are not groomed by carpenter bee. The percentage of female infested is 74.1%; infestation in females do not decrease mating and nesting performances. Four nests in canes (5.1% of total nests; 0.4 nest/year) was infested, (18 cells; 3.0%; 0.23 per nest; 1.8 per year). The mortality due to S. cerambycina is very low. Adults within the 4 X. violacea nests caused the death of eggs and larvae infested; adults feeds on pollen and pollen paste stored by X. violacea female; for these reasons S. cerambycina adults must be considered a parasites-commensales. Also for hypopi-X. violacea adult interactions, there are damages for the host, but only in the case of physio-energetical deficit of the host. The transmission of mites happens with the following modality: a) during copula; b) during flower visits; c) during recovery in winter or temporary shelters; d) inside nest heredity.
Keywords: Xylocopa violacea; Sennertia cerambycina; Phoresy; lnfestation effects; Hypopi transmission